Growth Stimulating Effects of Nitrogen Fixing Bacteria (Biofertiliser) on Oak Seedlings - Pandey, R. K.; Bahl, R. K.; Rao, P. R. T. (Indian Forester, 1986)
It is demonstrated here that a commercially available soil inoculant of nitrogen fixing bacteria, Azotobacter chroococcum promotes growth of Q. Serrata seedlings so much so that 106% more leaves were harvested from the seedlings inoculated with Azotobacter. There was also 15.38% increase in shoot length and 28.6% increase In root length. The dry weight of shoot and root also increased upto 45% and 70.7% respectively. This nursery trial warrants determination of the effectiveness of Azotobacter in commercial field applications to increase soil nitrogen of forest and range sites having Q. serrato which may in turn help in increasing the productivity of Oak-Tasar Silk.